(3GdCbQGHGPjf Ydi JQjJH GdYdds - (3eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO, GdfLjH GdSeQbfOj , J (B619 (3g` s
(3ChdgG (B:s
(3COhjI Ydd GdQCS (B: (3MH GdbhbGjG , GdCOhGA GdQCS GdGeJdGFjI ef GdQWhHI CjGQfL ajbQG , YTQI OQGge , TMe GdMfXd KdGKI OQGge hKdK s
(3BNQgG (B:s
(3hbO jSbi OGfbkG ef GdPGQGQjL eY OGfb ef GdYOS GdebTQ HeGA aGJQ HYO Cf jfbY GdPGQGQjM ai GdQGFH jhekG hdjdI , hjHOd GdQGFH hjaYd KdGK eQGJ , ajchf cGajkG Ef TGA Gddg JYGdi s
(3GdbSe GdSGOS ef GdfLjHjGJs
(3hbO bhHdJ MSH GdWGbI Ydi fSNI GdCUd HgG HYV GdVHWs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
Keywords: (3GdWHs